2019
DOI: 10.1038/s41598-018-37267-2
|View full text |Cite
|
Sign up to set email alerts
|

On the convective heat and zero nanoparticle mass flux conditions in the flow of 3D MHD Couple Stress nanofluid over an exponentially stretched surface

Abstract: Three dimensional problems reflect more imperative understanding to real world issues in comparison to two dimensional problems. Keeping this fact in mind, a mathematical model is designed to deliberate the 3D magnetohydrodynamic couple stress nanofluid flow with joule heating and viscous dissipation effects past an exponential stretched surface. The analysis is performed keeping in mind the physical effects of Brownian motion and thermophoresis combined with convective heat condition. This paper also distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 49 publications
(33 reference statements)
1
32
0
Order By: Relevance
“…The flow of viscoelastic nanofluid with analysis of entropy generation past an exponential stretched surface was discussed by Suleman et al [8]. Farooq et al [9] deliberated the flow of Newtonian fluid with the amalgamation of nanoparticles by utilizing the BVPh 2.0 technique and many therein [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The flow of viscoelastic nanofluid with analysis of entropy generation past an exponential stretched surface was discussed by Suleman et al [8]. Farooq et al [9] deliberated the flow of Newtonian fluid with the amalgamation of nanoparticles by utilizing the BVPh 2.0 technique and many therein [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the fluid velocity decreases with an enhancement in the magnetic field parameter. Many similar studies can be found in the literature on the importance of the boundary layer flow due to starching of a surface in the presence of Lorentz force with numerous heat transfer effects …”
Section: Introductionmentioning
confidence: 67%
“…Dawar et al [22] addressed the flow of nanofluid over a porous extending sheet with radiation influence. Ramzan et al [23] examined the MHD nanofluid flow using the couple stress effect. Sajid et al [24] examined nanofluid flow over a radially extending surface.…”
Section: Introductionmentioning
confidence: 99%